Generation of One-Dimensional Terahertz Airy Beam by Three-Dimensional Printed Cubic-Phase Plate - Liting Niu; Changming Liu; Qiao Wu; Kejia Wang; Zhengang Yang; Jinsong Liu (IEEE Photonics Journal, 2017)
We first present the one-dimensional (1-D) terahertz (THz) Airy beam with a 0.3-THz continuous wave. The required phase modulation and the optical Fourier transform are implemented with a 3-D printed cubic-phase plate (CPP) and a cylindrical lens, respectively. According to the parameter of the designed CPP, we numerically calculate the intensity distributions of the 1-D THz Airy beam in the free space. The experimental results show a good accordance with the theoretical ones. Additionally, by blocking part of the generated 1-D Airy beam with a metal screen, the beam exhibits a self-healing property, i.e., tends to reform during propagation.